2015
DOI: 10.7554/elife.08150
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell infection by HIV contributes over half of virus infection

Abstract: Cell-to-cell viral infection, in which viruses spread through contact of infected cell with surrounding uninfected cells, has been considered as a critical mode of virus infection. However, since it is technically difficult to experimentally discriminate the two modes of viral infection, namely cell-free infection and cell-to-cell infection, the quantitative information that underlies cell-to-cell infection has yet to be elucidated, and its impact on virus spread remains unclear. To address this fundamental qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 32 publications
6
144
0
Order By: Relevance
“…Along this line of thought, SFI antibodies may limit virus dissemination. A recent report documented that cell-to-cell infection by HIV-1 contributes to over half of the virus infection compared to cell-free virus infection and suggested that solely blocking cell-free virus infection in the absence of a cell-to-cell block would only partially limit virus dissemination (31). This conclusion may be applicable to viruses other than HIV, such as herpesviruses (e.g., HCMV and herpes simplex virus [HSV]).…”
Section: Discussionmentioning
confidence: 86%
“…Along this line of thought, SFI antibodies may limit virus dissemination. A recent report documented that cell-to-cell infection by HIV-1 contributes to over half of the virus infection compared to cell-free virus infection and suggested that solely blocking cell-free virus infection in the absence of a cell-to-cell block would only partially limit virus dissemination (31). This conclusion may be applicable to viruses other than HIV, such as herpesviruses (e.g., HCMV and herpes simplex virus [HSV]).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, it was suggested that merely blocking cell-free virus infection in the absence of cell-tocell blocking would only partially limit HIV virus dissemination [81].…”
Section: Immune Response To Pc and Protection From Hcmv Infection/dismentioning
confidence: 99%
“…It has recently been reported that >50 % of HIV dissemination occurs cell-to-cell rather than through cell-free virus infection [81]. Following this line of thought, we tested the dissemination-inhibiting activity of HCMV-neutralizing antibodies, both mAbs and convalescent-phase sera from primary infections, by using three different assays: (i) plaque formation (cell-to-cell spreading) inhibition (PFI) ( [74,79] (Fig.…”
Section: Antibody Response To Pc and The Other Glycoprotein Complexesmentioning
confidence: 99%
“…Cell-free HIV-1 infects both T cells and MDDCs, but infection is more efficient after cell-to-cell transfer (26,27). Using mathematical models, Iwami et al estimated that cell-to-cell transfer of HIV-1 contributes to 60% of viral infection (28). In contrast, cell-free HTLV-1 is poorly capable of infecting either CD4 ϩ T cells or MDDCs (20,29,30).…”
Section: Cell-free or Cell-associated Viruses Use Specific Entry Andmentioning
confidence: 99%